The Bucharest Stock Exchange: A starting point in structuring a valuable CSR index - Mirela Clementina Panait; Marian Cătălin Voica; Eglantina Hysa; Alfonso Siano; Maria Palazzo (Journal of Risk and Financial Management, 2022)
The aim of this article was to identify the role and specific mechanisms of the stock exchange in promoting corporate social responsibility (CSR) and CSR communications among companies listed on the Romanian capital market given country membership of the European Union. Taking into account the quality of the Bucharest Stock Exchange (BSE) as a member of the Sustainable Stock Exchanges, as well as BSE's concerns about promoting CSR, a CSR index was built to capture the specific actions of companies listed on this market. The public companies were considered representative for the promotion of CSR based on their size and other relevant features. The index can be seen by companies that can further develop it, test its validity, and employ it as a tool to reassure investors who will decide to spend their money to buy shares and stocks of organizations ranked in the BSE.
Keywords: 330; CSR; CSR communications; CSR index; Bucharest Stock Exchange (BSE); investors